ВИЗНАЧЕННЯ ВИТКОВИХ ЗАМИКАНЬ ОБМОТКИ СТАТОРА АСИНХРОННИХ ДВИГУНІВ НА ОСНОВІ МЕТОДУ КОМПЕНСАЦІЇ МАГНІТНОГО ПОЛЯ - Титко, О.І.; Худяков, А.В. (Інститут електродинаміки НАН України, Київ, 2017)
Based on the analysis of physical design characteristics of the electromagnetic field in the stator teeth crowns in the air gap induction-squirrel-cage motor. The new diagnostic options based on different forms of representation of the electromagnetic field in the air gap of motor, having circuit turns the stator winding shown their benefits. References 7, figures 3, tables 2.